Effects of amitriptyline on ventricular fibrillation threshold, effective refractory period, diastolic threshold and sinus node function in dogs - XIN Hong-bo; LIU Shi-fang (Acta Pharmacologica Sinica; Vol 7, No 6 (November 1986): Acta Pharmacologica Sinica, 2016)
The effects of anitriptyline (Ami) on electrical ventricular fibrillation threshold (VFT), ventricular effective refractory period (VERP), ventricular diastolic threshold (VDT) and corrected sinus recovery time (CSRT) were studied in dogs. Ami (3 mg/kg, iv) increased VFT (peak value: 8.2+/-5.8 V, P